Sustaining eSports Industry and Regulatory Focus: Empirical Evidence From Chinese Universities - Zhao, Gongyan; Cheng, Yue; Liu, Xingguo; Meng, Wentao (Frontiers in Psychology, 2022)
This study examined the factors affecting the attitude and behavioural intentions towards electronic sports (esports) among students of higher education institutions based on the Technology Acceptance Model (TAM). The conditional impact of preventive regulatory focus was analysed in various aspects developed on the regulatory focus theory. These aspects comprised perceived usefulness, perceived ease of use, and perceived risk on the attitude towards esports. Accordingly, data was collected from 293 students of higher education institutions in China’s Henan Province, presenting a 54.56% response rate. The PLS-SEM analysis was subsequently implemented to confirm the proposed hypotheses. The empirical findings confirmed the significant positive impact of perceived usefulness and perceived ease of use on the attitude towards esports. However, perceived risk negatively affected the attitude towards esports. Meanwhile, the findings on the moderating hypotheses found a negligible impact on preventive regulatory focus. This impact was found explicitly on the perceived usefulness-perceived ease of use link with attitude towards esports. However, the preventive regulatory focus negatively moderated the perceived risk attitude towards esports. Finally, the implication and limitations were illustrated at the end of the paper.